1991
DOI: 10.1002/ajim.4700200107
|View full text |Cite
|
Sign up to set email alerts
|

First‐aid reports of acute chlorine gassing among pulpmill workers as predictors of lung health consequences

Abstract: Workers in pulpmills can be exposed to a multitude of gases hazardous to respiratory function, the most common of which is chlorine gas. First-aid reports of acute gas overexposure incidents ("gassings") over an 8 year period were used to generate exposure data on a group of pulpmill workers whose respiratory function had been studied cross-sectionally in 1981 and 1988. Three hundred forty-eight incidents representing 174 workers were identified, 78% of these being treated solely by the first-aid attendant wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
40
0
3

Year Published

1993
1993
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 9 publications
1
40
0
3
Order By: Relevance
“…We may have missed reports of some high-exposure events that did not result in symptoms, and we may have included some relatively low-exposure events that were associated with symptoms. In a study of acute chlorine gassings among pulp mill workers, Salisbury et al (35) found that a self-reported history of gassings was not as strong a predictor of decrements in pulmonary function and the frequency of respiratory symptoms as a first-aid report of gassing incidents. Since we used self-reports of gassing events rather than more objective measures, we may have underestimated the risk of noninfectious rhinitis in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…We may have missed reports of some high-exposure events that did not result in symptoms, and we may have included some relatively low-exposure events that were associated with symptoms. In a study of acute chlorine gassings among pulp mill workers, Salisbury et al (35) found that a self-reported history of gassings was not as strong a predictor of decrements in pulmonary function and the frequency of respiratory symptoms as a first-aid report of gassing incidents. Since we used self-reports of gassing events rather than more objective measures, we may have underestimated the risk of noninfectious rhinitis in this study population.…”
Section: Discussionmentioning
confidence: 99%
“…Reactions with 0-6 and N-2 of guanine and N-6 of adenine have also been reported. The following products have been isolated from the reaction of sulfur mustard with DNA (5-18) (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) Sulfur mustard, because of its bifunctional nature, is more cytotoxic than is its monofunctional analogue. The molecular basis for this greater toxicity is the ability of sulfur mustard to form interstrand cross-links between guanines of the double helix, which prevents strand separation during replication.…”
Section: Veterans At Riskmentioning
confidence: 99%
“…It involves the reaction of acetylene with arsenic trichloride, by using aluminum chloride as a catalyst. The reaction yields three principal products (5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19):…”
Section: Lewisitementioning
confidence: 99%
See 2 more Smart Citations